Dog Training Intervention Shows Social-Cognitive Change in the Journals of Incarcerated Youth - Syzmanski, Tiffany; Casey, Rita J.; Johnson, Amy; Cano, Annmarie; Albright, Dana; Seivert, Nicholas P. (Frontiers in Veterinary Science, 2018)
There is limited research assessing the effectiveness of Animal-Assisted Therapy in at-risk adolescent populations. In a recent study, 138 adjudicated adolescents participated in a randomized controlled trial of an animal-assisted intervention, in which participants either trained shelter dogs (Teacher’s Pet group) or walked the dogs (control group), with both groups participating in classroom work related to dogs (Seivert, Cano, Casey, Johnson, & May, 2018). Journal writing was a part of class activities for all youth in the study. Conventional assessments of youth behavior made by staff or youth themselves did not demonstrate the expected differences between the groups favoring the dog training group, as youth in both groups showed a significant increase in staff and youth rated internalizing behavior problems and empathy from the beginning to the end of the project. (Seivert et al., 2018). However, subsequent analysis of the journal content from 73 of the adjudicated youth reported here, did reveal significant differences between treatment and control groups, favoring the Teacher’s Pet group. Youth participating in the dog training intervention showed through their journal writing greater social-cognitive growth, more attachment, and more positive attitudes toward the animal-assisted intervention compared to youth in the control group. The 73 youth whose journals were available were very similar to youth in the larger group. Their results illustrate that journaling can be a useful method of assessing effects of similar animal-assisted interventions for at-risk youth. Writing done by youth receiving therapy appeared to promote self-reflection, desirable cognitive change, and prosocial attitudes that may signify improving quality of life for such youth. The expressive writing of participants could reveal important effects of treatment beyond the behavioral changes that are often the targeted outcomes of animal-assisted interventions.